Chapter 3. Principles and Practices of Irrigation Management for Vegetables: VPH ch. 3, CV297, rev. 6/2024 - Zotarelli, Lincoln; Dukes, Michael D.; Simonne, Eric H. (EDIS, 2024)
Chapter 3 of the Vegetable Production Handbook of Florida